2006
DOI: 10.1029/2006gl027519
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of MODIS land surface temperature with in situ observations

Abstract: MODerate resolution Imaging Spectroradiometer (MODIS) land surface temperatures (LSTs) are compared to in situ observations during the Coordinated Enhanced Observing Period (CEOP). The purpose is to test the utility of global enhanced station data to provide additional information on the consistency of large volumes of remotely sensed data. While comparisons are limited by unresolved spatial and temporal representativeness, many of the comparisons are quite favorable, especially in mid‐latitude regions. We not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…The assessment study of remotely sensed land surface temperature by Trigo et al [51] has found that the both SEVIRI and MODIS tend to underestimate local measurements, with colder values obtained with MODIS. It agrees with the results of the study [67] that compare MODIS LST with ground measurements over land. As an important input in the method, the cold bias of MODIS LST product will influence the values of the estimated soil and vegetation temperature.…”
Section: Validation and Discussionsupporting
confidence: 81%
“…The assessment study of remotely sensed land surface temperature by Trigo et al [51] has found that the both SEVIRI and MODIS tend to underestimate local measurements, with colder values obtained with MODIS. It agrees with the results of the study [67] that compare MODIS LST with ground measurements over land. As an important input in the method, the cold bias of MODIS LST product will influence the values of the estimated soil and vegetation temperature.…”
Section: Validation and Discussionsupporting
confidence: 81%
“…It reveals that the LSTs retrieved during daytime are closer to the GSTs than during nighttime with LSTs only 1 • C higher than GSTs, but the high variability shows that LSTs are very variable around this 1 • C (from (Table 5). It shows that at nighttime, problems appear that do not exist during daytime (Ackerman et al, 1998). Comparing data acquired within the same hour (not shown in tables) indicates that 13:00 and 14:00 h are the hours at which the mean differences between LST and GST are the smallest and correlations highest, independently of the station in Alaska, while it is at 12:00 h for the Québec stations.…”
Section: Comparison Of Daytime Nighttime and Daily Mean Gst With Lstmentioning
confidence: 96%
“…The latter study found that the night-time Aqua-MODIS LST had smaller differences in surface air temperature than the Terra-MODIS LST. Comparing these results, as well as reports from other, less-representative studies (e.g., [25]), one has to be cautious about systematic urban biases in the MODIS LST data. This question is rather unclear in the present context because, as mentioned above, high-latitude cities generally have no in situ observational networks and no detailed UHI studies have been conducted there previously.…”
Section: Methodsmentioning
confidence: 81%
“…It has high calibration accuracy in multiple thermal infrared bands designed for retrievals of LST and atmospheric properties [23]. Despite some noted difficulties and inaccuracies [24,25], the LST data retrieved by the MODIS sensors aboard the Terra (EOS AM) and Aqua (EOS PM) NASA satellites are widely used for UHI studies [16,26,27].…”
Section: Introductionmentioning
confidence: 99%